2012
DOI: 10.1200/jco.2011.38.0287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Survival After Colorectal Cancer Diagnosis: The Cancer Prevention Study-II Nutrition Cohort

Abstract: This study suggests that prediagnosis BMI, but not postdiagnosis BMI, is an important predictor of survival among patients with nonmetastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
199
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(218 citation statements)
references
References 25 publications
10
199
2
1
Order By: Relevance
“…Detailed descriptions of these clinical and epidemiologic factors are presented elsewhere (14)(15)(16)(17)(18)(19)(20). Participants were stratified by tissue accrual status (accrued versus not accrued) and method of diagnosis confirmation (medical record versus state cancer registry linkage) and compared using Pearson c 2 tests or t tests, as appropriate.…”
Section: Methods For Establishing the Colorectal Tissue Repository Inmentioning
confidence: 99%
“…Detailed descriptions of these clinical and epidemiologic factors are presented elsewhere (14)(15)(16)(17)(18)(19)(20). Participants were stratified by tissue accrual status (accrued versus not accrued) and method of diagnosis confirmation (medical record versus state cancer registry linkage) and compared using Pearson c 2 tests or t tests, as appropriate.…”
Section: Methods For Establishing the Colorectal Tissue Repository Inmentioning
confidence: 99%
“…A diet rich in fruits, vegetables, poultry, fish, whole grain, and poor in red meat and concentrated sweets was associated with better outcomes with regard to cancer recurrence or death. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Another important aspect of survivorship care is health promotion. Evidence suggests that noncancer comorbidities have a negative impact on overall quality of life and long-term survival when compared with the cancer diagnosis itself.…”
Section: Survivorshipmentioning
confidence: 99%
“…Interestingly, post diagnosis BMI (based on weight reported) was not associated with all-cause or cancer-specific mortality. The authors concluded that the BMI before but not after diagnosis was an important predictor of survival among patients with non-metastatic CRC [31]. …”
Section: Nutrition and Colon Cancermentioning
confidence: 99%
“…Recently, Campbell et al [31] analyzed the data of the Cancer Prevention Study-II Nutrition Cohort including 184,000 participants and evaluated the association of BMI before and after diagnosis of non-metastatic CRC with survival in this prospective cohort. The authors found that an increased BMI before CRC diagnosis was associated with a higher risk of mortality resulting from all causes, related to CRC or cardiovascular diseases.…”
Section: Nutrition and Colon Cancermentioning
confidence: 99%